Analyzing Students Autonomy and Critical Thinking in Blend-ed Learning Environments: A Case Study of Edu Global School High School Students - Arif Nugraha, Laode; Siti Hajaroh, Yanti (Journal of English Education and Teacher Trainer, 2025)
This writing specifically investigates the development of students' autonomy and critical thinking in a blended learning environment at Edu Global School. The study employs qualitative methods to thoroughly describe students' self-regulated learning strategies, their capacity to establish personal learning objectives and critical thinking, and the influential role of teacher support in fostering autonomy. Data was meticulously gathered through semi-structured interviews and comprehensive classroom observations. The compelling findings indisputably demonstrate that while blended learning presents significant opportunities for independent learning, students require consistent guidance to fully develop self-regulatory and critical thinking skills. The study highlights the role of digital tools and teacher facilitation in promoting autonomous and critical learning behaviors with recommendations for enhancing critical thinking and self-directed learning among high school students.